The Effectiveness of Literature Circles (LC) Strategy on Learners’ Reading Comprehension at the VIII Grade of UPTD SMP N 3 Kec. Guguak - Julian, Intan; Melani, Melyann; Reflinda, Reflinda; Roza, Veni (Education Achievement: Journal of Science and Research, 2024)
This research was conducted based on problems found by researcher in the learning process about reading comprehension using the Literature Circles (LC) strategy. It found that learners had problems when understanding the text although the teacher taught by using the Literature Circles strategy. Next, learners had difficulty to make a summary although the Literature Circles strategy was used. Last, in applying the Literature Circles strategy teacher had tried to help learners to comprehend some words that learners did not know from the text, but learners still tend to have difficulty in understanding those words. The purpose of this research was to see the effectiveness  of using the Literature Circles strategy in teaching reading comprehension for VIII grade at UPTD SMP N 3 Kec.Guguak. The method used in this research was descriptive quantitative research, which aims to describe the significant effect of using Literature Circles (LC) strategy on reading comprehension learners. The population of this research were all of the learners in VIII grade of UPTD SMP N 3 Kec.Guguak.  Then, the instrument used in this research was a reading comprehension test. The finding reveals that the use of Literature Circles strategy is effective to improve reading comprehension at VIII grade of UPTD SMP N 3 Kec. Guguak. It shows that in indicators the identifying the main idea and identifying generic structure in the text get the highest percentage of score (91.6%). Meanwhile, the result percentage of average score in indicator the vocabulary in the context get the lowest percentage of score (57.3%). Even though there is low score in those one reading comprehension’s indicator, but the total percentage of average score from all indicators in reading comprehension learners is 79.5%. According to the table of interpretation of the effectiveness percentage, 79.5% indicated ‘Effective” category. It means in using Literature Circles strategy is effective to improve the learners reading comprehension.